The Frequency of Ear, Nose, Throat, Head and Neck Lesions of Tuberculosis in the Eastern District of Libya. - Abdulkarim, Yosef H.; Fadallah, Marei M. (Libyan Journal of Science &Technology, 2025)
Tuberculosis (TB) in the head and neck region represents a diagnostic challenge as it can mimic many conditions, such as malignancy and chronic granulomatous diseases. Therefore, the clinician must have a high index of suspicion for head and neck TB increasing the awareness of health workers in Libya of how TB affects the head and neck areas and its common presenting features may prevent unnecessary delays in the diagnosis and treatment of these cases and improve their outcomes. Objective: Assess the frequency of ENT manifestations of tuberculosis. A cross-sectional observational study was conducted, and the cases were subjected to a detailed history and a head and neck examination. The data were analyzed to assess any association existing between the study variables and the prevalence of ENT, head, and neck manifestations of tuberculosis. The results of this study showed that, out of 168 cases of TB included in the study, 49 were positive for ENT, head, and neck tuberculosis. Tuberculous lymphadenitis was the most common TB manifestation in the head and neck region, accounting for 87.8% of positive cases. Laryngeal TB and TB abscesses of the deep neck spaces account for 4.1% and 4.1% of positive cases, respectively. TB otitis and nasal TB account for 2% and 2% of positive cases, respectively. Conclusion: TB in the head and neck region represents a diagnostic challenge, and a high index of suspicion is needed. All suspected cases should be investigated appropriately. Close cooperation between TB-related medical specialists is needed.